-8z-7z=-3z-5-9z

Simple and best practice solution for -8z-7z=-3z-5-9z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8z-7z=-3z-5-9z equation:


Simplifying
-8z + -7z = -3z + -5 + -9z

Combine like terms: -8z + -7z = -15z
-15z = -3z + -5 + -9z

Reorder the terms:
-15z = -5 + -3z + -9z

Combine like terms: -3z + -9z = -12z
-15z = -5 + -12z

Solving
-15z = -5 + -12z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '12z' to each side of the equation.
-15z + 12z = -5 + -12z + 12z

Combine like terms: -15z + 12z = -3z
-3z = -5 + -12z + 12z

Combine like terms: -12z + 12z = 0
-3z = -5 + 0
-3z = -5

Divide each side by '-3'.
z = 1.666666667

Simplifying
z = 1.666666667

See similar equations:

| x^2+3n=0 | | 18b^4=15 | | 6=8x-7 | | 5x+9=-2x+2 | | 18x-1=14x-21 | | 4x+9x-6x-5=30 | | -7y-2=-6y-5 | | X+6=7x+5 | | 12y+54x-6=0 | | 45+x=0.1(900+x) | | -4(1-3r)=-100 | | 4x^2+5x+c=0 | | 5y+3x=60 | | 55r^2+4r-3= | | 2(3x+6)=-14+8 | | 8/5/6-10/1/12= | | 3x+18=6x+24 | | 7x-4x+3=x-6+9 | | 2x+3-1=2x-2-(-x) | | x^2-33x+540=0 | | 13=3r+5+r | | 6x+20=172-4y | | 8xy-5xy= | | 6x+8-2x=-7x-15+x | | 6x+3y-2z=7 | | 5=r+5-1 | | 7x-2=2+3 | | 3x^2-363= | | -2p+7=5-8p-3 | | 7-4[5-(6y-3)]= | | y=7(x+a) | | 10=2*2*2*2*2-22 |

Equations solver categories